Changes in thiol/disulfide homeostasis in juvenile idiopathic arthritis. Issue 6 (20th May 2018) - Altinel Acoglu, Esma; Erel, Ozcan; Yazilitas, Fatma; Bulbul, Mehmet; Oguz, Melahat Melek; Yucel, Husniye; Karacan, Can Demir; Senel, Saliha
Abstract: Background: The pathogenesis of juvenile idiopathic arthritis (JIA) remains unknown, but imbalance between the oxidant and antioxidant defense systems may play a role. Measuring thiols in plasma provides an indirect indication of antioxidative defense. The aim of the present study was to investigate the association between JIA and dynamic thiol/disulfide homeostatic status. Methods: This case–control study involved 34 JIA patients and 30 age‐ and gender‐matched healthy controls. The patients were divided into subgroups according to Simplified Disease Activity Index (SDAI) score: active, SDAI > 3.3; remission, SDAI ≤ 3.3. Results: Native thiol and total thiol were significantly lower in the JIA group than in the control group ( P = 0.001). There was no significant difference in the disulfide/native thiol, disulfide/total thiol, and native thiol/total thiol ratios between the JIA and control groups ( P > 0.05). Based on SDAI score, 22 JIA patients were in the remission subgroup, and 12 JIA patients were in the active subgroup. Native thiol and total thiol were significantly lower in the active JIA subgroup than in the remission subgroup ( P = 0.001), but there were no significant differences in the other parameters. There was no significant difference in thiol and disulfide levels between systemic‐onset JIA and other JIA ( P > 0.05). Conclusions: Plasma thiol is lower in JIA patients, especially during periods of active disease, than in healthy controls, indicating that low thiol might be an important factor in the etiology of JIA and that antioxidant systems are negatively affected by inflammatory diseases, especially during periods of active disease.